College Entry by Blacks since 1970: The Role of College Costs, Family Background, and the Returns to Education - Kane, Thomas J. (Journal of Political Economy, 1994)
College enrollment of black 18-19-year-old high school graduates declined from 1980 through 1984 and then rebounded after 1984. This paper presents data from a time series of cross sections of 18-19-year-old youths from 1973 through 1988 to test the role of family background, direct college costs, local economic conditions, and returns to college in driving these trends. The evidence suggests that, on the one hand, increases in direct college costs were driving enrollment rates downward throughout the eighties. On the other hand, dramatic increases in average parental education for black youths exerted upward pressure on college enrollment by blacks, particularly in the latter half of the decade. The net effect of these two factors contributed to the pattern of decline and recovery observed during the eighties.